Pricing via processing or combatting junk mail - Dwork, Cynthia; Naor, Moni (CRYPTO '92: Proceedings of the 12th Annual International Cryptology Conference on Advances in Cryptology, 1992)
We present a computational technique for combatting junk mail in particular and controlling access to a shared resource in general. The main idea is to require a user to compute a moderately hard, but not intractable, function in order to gain access to the resource, thus preventing frivolous use. To this end we suggest several pricing Junctions, based on, respectively, extracting square roots modulo a prime, the Fiat-Shamir signature scheme, and the Ong-Schnorr-Shamir (cracked) signature scheme.